Targeted α-synuclein mRNA degradation by PMO-based RNA-degrading chimeras - Ning Wang; Shalakha Hegde; Zhichao Tang; Haiqing Liu; Gang Feng; Lili Niu; Bo Liu; Hanyu Li; Xiaodi Zhang; Kundlik Gadhave; Ramhari Kumbhar; Lan Jiang; et al. (Proceedings of the National Academy of Sciences, 2026)
α-Synucleinopathies are devastating neurodegenerative diseases characterized by pathological accumulation of a neuronal protein, α-synuclein (αSyn). Lowering soluble αSyn levels is a promising therapeutic strategy to limit aggregation and neurotoxicity, but directly targeting this protein is hindered by its intrinsically disordered structure and other factors, such as its conformational heterogeneity and intracellular drug delivery barriers. Consequently, increasing attention has been directed toward targeting the SNCA transcript, which encodes αSyn. Here, we developed phosphorodiamidate morpholino oligonucleotide (PMO)-based RNA-degrading chimeras (RDCs) that selectively bind the 5′ untranslated region of SNCA messenger RNA (mRNA) and recruit RNase L for targeted RNA degradation. Through the systematic evaluation of nine RDCs, we identified and optimized 4-D1, which effectively reduced SNCA mRNA and αSyn protein expression in HEK293T cells in an RNase L-dependent manner. 4-D1 lowered SNCA transcript and αSyn protein levels in both primary cortical neurons from humanized SNCA mice and in human induced pluripotent stem cell–derived cortical neurons. This reduction prevented prion-like seeding induced by patient-derived αSyn fibrils and protected neurons from fibril-induced cytotoxicity. Finally, in vivo studies confirmed the efficacy of 4-D1 in reducing αSyn mRNA expression in humanized SNCA mice. These findings indicate that PMO-based RDCs may represent a promising therapeutic modality for α-synucleinopathies.